Consumer color preferences and the economics of bean consumption in malawi - Mbamba, Austin (Kansas State University, 2019)
Different dry bean crop varieties with different colors are produced in Malawi. Yet, little is known about the drivers of consumer preferences for the different dry bean varieties grown based on color. Literature shows that consumers link bean color to taste, cooking time, gravy quality and other desirable characteristics. The main objective of this research was to assess factors that determine consumption of different types of dry beans in Malawi based on color to determine preferences for different consumer segments and hence the potential value of these preferences communicated across the dry bean supply chain, to enhance the probability of success for breeders’ efforts and the bean value chain’s initiatives. The research used survey data that was collected by the Bean Value Chain Research Network in Lilongwe District, Malawi. The sample size of the dataset was 687 households from three different economic strata. The research focused on four dry bean colors: Red, Red Mottled, White and Cream Mottled bean. These were found to be the most prominent colors by sales and stated preference in Malawi. Two econometric approaches were used in the data analysis. A bivariate analysis using Pearson’s chi-square was used to test the significance of the association between bean consumption (dependent variable) and household as well as product characteristics explanatory variables. A logit model was run on each of the four color types to assess the extent to which the explanatory variables influence consumer preferences for alternative colors of dry bean products. Results showed that 40.8% of the respondents consumed red beans, 12.6% consumed red mottled, 14.6% consumed White and 32% consumed Cream mottled beans. In terms of demographic characteristics, respondents’ marital and employment status as well as household size were found to have no significant influence the consumption of all the four colors. Being educated decreased probability of consuming white and cream mottled beans. Household characteristics were also found to influence preferences for color. For example, households in low and middle-income households were shown to have a lower likelihood of consuming white beans. The characteristics of the beans were also important in influencing preferences. For example, medium grain size beans influenced preference for red beans while fast cooking beans negatively affected the consumption of mottled red beans. The results provide insights for bean breeders in their attempts to contribute to increased producer incomes through a careful response to consumer preferences and not just producer demands for agronomic traits.
Keywords: Bean Value Chain; Malawi; Legume; Economics; Agronomic traits